Highly Emissive Far Red/Near‐IR Fluorophores Based on Borylated Fluorene–Benzothiadiazole Donor–Acceptor Materials. Issue 35 (27th July 2016) - Crossley, Daniel L.; Vitorica‐Yrezabal, Inigo; Humphries, Martin J.; Turner, Michael L.; Ingleson, Michael J.
Abstract: Stille, Suzuki–Miyaura and Negishi cross‐coupling reactions of bromine‐functionalised borylated precursors enable the facile, high yielding, synthesis of borylated donor–acceptor materials that contain electron‐rich aromatic units and/or extended effective conjugation lengths. These materials have large Stokes shifts, low LUMO energies, small band‐gaps and significant fluorescence emission >700 nm in solution and when dispersed in a host polymer. Abstract : The perfect couple : Cross‐coupling enables the high yielding synthesis of borylated donor–acceptor materials that contain electron‐rich aromatics units and/or extended effective conjugation lengths. These materials have large Stokes shifts, low LUMO energies, small band‐gaps and significant fluorescence emission >700 nm in solution and in the solid state.